The Influence of Social-Economic Factors on the Determination of Financial Technology in Banda Aceh - ALIASUDDIN; Nanda RAHMI; NASHRILLAH (Communications of International Proceedings, 2021)
This study aims to identify the socioeconomic factors that influence the selection of financial technology in Banda Aceh Municipality. The chi-squares distribution is used to estimate the effect of these variables on the determination of financial technology. The number of respondents in this study was 415 people with a minimum age of 25 years. The estimation results prove that males are more likely to borrow money through financial technology if they have low education compared to females. Poor households will borrow more than non-poor households. High interest rates do not reduce financial technology lending. Furthermore, respondents with precarious jobs will tend to borrow financial technology compared to households with permanent jobs. Financial technology legality is a significant factor in borrowing through financial technology. Furthermore, respondents want easy access to the financial technology lending process through the application or the web. Suggestions that this financial technology is better and does not harm the community, policymakers make regulations so that the existence of this financial technology does not cause harm to the community. In addition, it is necessary to enforce the law against illegal financial technology so that households are better protected from illegal financial technology activities. For financial technology companies, it is necessary to improve services with reasonable interest rates and easier access to the loan process.